Russian Seapower and ‘the Eastern Question’ 1827–41 - Daly, John C.K. author. aut Link
XVII, 314 p.
Keywords: Focusing on the Black Sea fleet between 1827-1841, this book assesses Russia's naval strength against other Mediterranean powers, especially the Ottoman Empire, arguing their limitations came from geographic, political and economic considerations. Primary and secondary sources are utilized.